Methamphetamine and sildenafil (Viagra) use are linked to unprotected receptive and insertive anal sex, respectively, in a sample of men who have sex with men. Issue 2 (30th March 2006) - Mansergh, G; Shouse, R L; Marks, G; Guzman, R; Rader, M; Buchbinder, S; Colfax, G N
Abstract : Objectives: There is evidence that methamphetamine and sildenafil (Viagra) use are associated with sexual risk behaviour among men who have sex with men (MSM). We investigated the association of methamphetamine, sildenafil, and other substance use with unprotected receptive and insertive anal sex among MSM by conducting an encounter specific analysis. Methods: Data were from a cross sectional, community based survey of MSM in San Francisco regarding behaviour during their most recent anal sex encounter. Mulitvariate regression analysed independent associations of specific substance use and demographic variables with unprotected anal sex behaviours. Results: The sample (n = 388) was diverse in race/ethnicity, age, income, education, HIV status, and homosexual/bisexual identification. More than half (53%) reported unprotected anal sex, including insertive (29%) and receptive (37%) during their most recent anal sex encounter; 12% reported unprotected insertive and 17% reported unprotected receptive anal sex with an HIV discordant or unknown partner. Methamphetamine was used by 15% and sildenafil was used by 6% of the men before or during the encounter; 2% used both drugs. In multivariate analysis controlling for demographic factors and other substance use, methamphetamine use was associated with unprotected receptive (odds ratio (OR), 2.03; 95% confidence interval (CI), 1.09 to 3.76) and sildenafil use was associated with unprotected insertive (OR, 6.51; CI, 2.46 to 17.24) anal sex. Effects were stronger with HIV discordant or unknown sex partners specifically. Conclusion: Encounter specific associations of methamphetamine and sildenafil use with unprotected receptive and insertive anal sex, respectively, indicate the importance of assessment specificity and tailoring risk reduction efforts to address certain drugs and sexual behavioural roles among MSM.